A STABILITY-INDICATING AND VALIDATED REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR THE SIMULTANEOUS ESTIMATION OF PHENYLEPHRINE AND FEXOFENADINE IN BULK AND TABLET DOSAGE FORMS - KUMAR B, SAI; G, Jyothi; Rao B, Sreenivasa (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A simple and accurate stability indicating reversed-phase high-performance liquid chromatography method was developed and validated for the simultaneous estimation of phenylephrine and fexofenadine in pharmaceutical dosage forms. Methods: Chromatography was carried out on an ODS C-18 column (4.6 mm×250 mm, 5 µ particle size) with a isocratic mobile phase composed of orthophosphoric acid buffer, acetonitrile, (75:25% v/v) at a flow rate of 1 mL/minutes. The column temperature was maintained at 30°C and the detection was carried out using a photodiode array detector at 210 nm. Results: The retention times for phenylephrine and fexofenadine were 2.096 minutes and 4.241 minutes, respectively. The percentage recoveries of phenylephrine and fexofenadine were 100.63% and 99.84%, respectively. The relative standard deviation for assay of tablets was found to be <2%. The detection and quantification limits were found to be 0.10 and 0.31 µg/mL for phenylephrine and 0.01 and 0.03 µg/mL for fexofenadine, respectively. Conclusion: Thus, the method was fast, accurate, precise, and sensitive; hence, it can be employed for routine quality control of tablets containing both drugs in quality control laboratories and pharmaceutical industries. Keywords: Phenylephrine, Fexofenadine, Stability indicating method, Validation method, Reversed-phase high performance liquid chromatography.